Multi-functional, highly fluorescent carbon dots from enokitake mushroom (Flammulina velutipes) for metal ion sensing and imaging applications - Pacquiao, Melvin R.; De Luna, Mark Daniel G.; Paoprasert, Peerasak (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Carbon dots are optically unique materials that can be prepared from a variety of raw natural materials and applied for several applications. In this work, highly fluorescent and water-soluble carbon dots were prepared from enokitake mushroom and applied for Cr6+ sensing and imaging applications. The carbon dots were synthesized via a one step hydrothermal method in the presence of dilute sulfuric acid solution. The effects of reaction time, temperature, and acid content on the quantum yield of carbon dots were investigated. The carbon dots produced showed blue photoluminescence with the best quantum yield of 11.4 percent. Upon passivation with tetraethylenepentamine, the quantum yield increased to 39 percent. The spherical carbon dots have an average diameter of about 4 nm. Carbon dots were found to be sensitive to Cr6+ with a limit of detection of 0.73134 uM and a linear range of 10-50 UM. A paper-based device was constructed and used to determine Cr6+ as low as 100 uM. In addition, the carbon dots were tested as fingerprint detection agent and fluorophore for the manufacture of fluorescent plastics. Based on these results, we demonstrated that enokitake mushroom, a healthy ingredient in Eastern cuisines, can be used to produce multifunctional carbon dots for diverse applications.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman
Keywords: Nanostructured materials; Mushrooms; Metal ions; Carbon dots